Development of a regionalized dynamic weighting method for the environmental impact of alternative protein sources - Francis, Aditya; Ghnimi, Sami; Smetana, Sergiy (Frontiers in Sustainable Food Systems, 2024)
Accurate environmental analysis is central to addressing food product impacts, yet uncertainty shrouds the effectiveness of life cycle assessment (LCA) weighting methods, particularly for alternative protein foods and different countries. Our approach characterizes environmental impact weighting based on total or specific production impacts at the country level, facilitating relevance assessment. We have developed an innovated methodology to calculate weights for alternative foods such as crickets, mealworms, black soldier flies, cultured meat, chlorella, and spirulina. This method integrates their country-level eco-potential linked to environmental impacts, and addresses challenges in existing methodologies-policy changes, contextual adaptation, method specificity, intangible values. Relative impact weights, normalized by arable land and population, cover greenhouse gas emissions, land use, water use and energy use. Eco-potential points for alternative protein sources are derived by dividing their impact values by the relative country-level weights. In addition, eco-potential points for conventional protein sources are calculated for comparison, highlighting disparities. The results show a dynamic eco-potential influenced by evolving country-level per capita impacts that influence food product impacts. Comparison of literature based LCAs with our weighted country-level impacts highlights an alignment between absolute emissions and relative impact weightings in certain cases. Moreover, we have developed a parallel methodology to calculate eco-potential points for selected alternative food proteins based on protein supply in countries. This calculation is based on 17 years of data and multiplies the protein supply by the average environmental impact of selected sources (GHGE, water, land and energy use). This results in country-level weighted impacts (CWI), or eco-potential points that are aligned with protein supply. Combining the CWI from the four indicators gives the combined eco-potential values for selected alternative proteins.